Cultural competence a primer for educators - Moule, Jean (Wadsworth Cengage Learning, 2012)
This edition covers the basics of multicultural education, making it easy for instructors to assign as a main text or use in conjunction with other books. The author gives special attention to the psycho-social dimensions of teaching culturally diverse populations.